Effect of Micronized Purified Flavonoid Fraction Therapy on Endothelin-1 and TNF-α Levels in Relation to Antioxidant Enzyme Balance in the Peripheral Blood of Women with Varicose Veins - Pietrzycka, Agata; Kozka, Mariusz; Urbanek, Tomasz; Stepniewski, Marek; Kucharzewski, Marek (Current Vascular Pharmacology, 2015)
Objective The aetiology of varicose veins involves various factors and pathomechanisms including endothelial cell activation or dysfunction, venous hypertension, vein wall hypoxia, shear stress disturbances, inflammatory reaction activation or free radical production. To improve our understanding of the mechanisms of potential pharmacological interventions for chronic venous disease, we evaluated the influence of micronized purified flavonoid fraction (MPFF) on the relationship between antioxidant enzyme balance, endothelin-1 (ET-1) and tumour necrosis factor-α (TNF-α) levels. Material and Methods Blood samples were obtained from 89 women with primary varicose veins; 34 were treated with MPFF and 55 did not receive any phlebotropic drug treatment. For the evaluation of the blood antioxidant enzyme balance, catalase (CAT) and superoxide dismutase (SOD) activity was assessed and the CAT/SOD ratio was calculated. Results Patients taking MPFF had significantly lower ET-1 levels than those not taking MPFF [median (25-75th quartile): 24.2 (22.30-27.87) vs 37.62 (24.9-44.58) pg.ml-1; p <0.05]. In those taking MPFF, a higher CAT/SOD ratio [39.8 (24.7-72.6) vs 28.8 (16.3-57.7); p<0.05] and a lower TNF-α concentration [6.82 (4.42-13.39) vs 12.94 (6.01-27.33) pg.ml-1; p<0.05] was also observed. In women not taking MPFF, ET-1 levels increased with the CAT/SOD ratio. In those taking MPFF, the ET-1 level was stable at approximately 25.0 pg.ml-1¬ up to a CAT/SOD ratio of 100. TNF-α level increased continuously with an increasing CAT/SOD ratio; however, the highest levels of TNF-α were observed in women not taking MPFF. Conclusion We demonstrate the ability of MPFF to effectively lower the levels of ET-1 and TNF-α in patients with chronic venous disease. Further investigations are needed to define the therapeutic potential of MPFF including the potential effect on chronic subclinical inflammation, antioxidant imbalance and vascular dysfunction during the development of chronic venous disease.
Keywords: catalase